Minimally Invasive Ablative Therapies for Definitive Treatment of Localized Prostate Cancer in the Primary Setting - Eugene W. Lee; William C. Huang (Prostate Cancer, 2011)
Traditionally, the patient with a new diagnosis of localized prostate cancer faces either radical therapy, in the form of surgery or radiation, or active surveillance. A growing subset of these men may not be willing to accept the psychological burden of active surveillance nor the side effects of extirpative or radiation therapy. Local ablative therapies including cryotherapy, high-intensity focused ultrasound, and vascular-targeted photodynamic therapy have emerged as a means for minimally invasive definitive treatment. These treatments are well tolerated with decreased morbidity in association with improvements in technology; however, long-term oncologic efficacy remains to be determined.